1993
DOI: 10.1203/00006450-199303000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Volume History on Measurements of Respiratory Mechanics Using the Interrupter Technique

Abstract: ABSTRACT. The importance of the viscoelastic properties of the tissues of the respiratory system has recently been recognized, and lung models have been produced to describe the resistive and viscoelastic properties of the lung. The pulmonary mechanics of 10 rabbits were studied using the interrupter technique to assess the effect of volume history on the resistive and viscoelastic elements of the respiratory system. The influence of the tone of the muscles of respiration was also studied. In healthy lungs, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
3
3
0
1
Order By: Relevance
“…However, changes in lung tissue mechanics following alveolar recruitment/derecruitment, interstitial edema, and/or parenchymal remodeling may be masked by an unknown and potentially variable chest wall component. Indeed, our study confirmed the substantial contribution of the chest wall to total respiratory damping and elastance for rabbits (16) and a proportionally smaller, but still important, contribution for rats (31). These chest wall contributions appear to bias the assessments of lung mechanical changes significantly (as much as 2-fold) when they are inferred from parameters reflecting the total respiratory system mechanics [Supplemental Fig.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, changes in lung tissue mechanics following alveolar recruitment/derecruitment, interstitial edema, and/or parenchymal remodeling may be masked by an unknown and potentially variable chest wall component. Indeed, our study confirmed the substantial contribution of the chest wall to total respiratory damping and elastance for rabbits (16) and a proportionally smaller, but still important, contribution for rats (31). These chest wall contributions appear to bias the assessments of lung mechanical changes significantly (as much as 2-fold) when they are inferred from parameters reflecting the total respiratory system mechanics [Supplemental Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Measurement of the difference between airway opening and esophageal pressures (P es ) as a surrogate of transpulmonary pressure offers the possibility to separate the mechanical properties of these two compartments. This approach has been successfully applied to humans (7, 10 -12, 14, 29), dogs (5,20,27), cats (17), rabbits (1,16), and rats (22,24,31). However, no such measurements have been performed in mice despite the rapidly increasing importance of this animal model in a wide variety of respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Although expiration is passive and inspiration is influenced by inertance and muscular drive, R int FV i was always lower than R int FV e , and muscular activity during the time of occlusion seems improbable. Freezer et al noted in their study 30 that the volume history of the lung may be important in determining the stresses distending the intrapulmonary air spaces. They observed in healthy, anesthetized, mechanically ventilated rabbits higher resistance of the respiratory system during passive expiration when performing an endinspiratory occlusion before the expiratory occlusion than when omitting it.…”
Section: Inspiration Vs Expirationmentioning
confidence: 97%
“…This was done to avoid the confounding effect of comparing respiratory mechanics during spontaneous breathing prior to intubation, with measurements taken during positive pressure ventilation postintubation. We would not expect our results to have been different if muscle relaxants had been used (16).…”
Section: Discussionmentioning
confidence: 71%